Neurologic Injury in Patients Treated With Extracorporeal Membrane Oxygenation for Postcardiotomy Cardiogenic Shock - Toivonen, Fanni; Biancari, Fausto; Dalén, Magnus; Dell'Aquila, Angelo M; Jónsson, Kristján; Fiore, Antonio; Mariscalco, Giovanni; El-Dean, Zein; Gatti, Giuseppe; Zipfel, Svante; Perrotti, Andrea; Bounader, Karl; et al. (Journal of cardiothoracic and vascular anesthesia, 2021)
OBJECTIVE: To investigate the frequency, predictors, and outcomes of neurologic injury in adults treated with postcardiotomy extracorporeal membrane oxygenation (PC-ECMO). DESIGN: A retrospective multicenter registry study. SETTING: Twenty-one European institutions where cardiac surgery is performed. PARTICIPANTS: A total of 781 adult patients who required PC-ECMO during 2010 to 2018 were divided into patients with neurologic injury (NI) and patients without neurologic injury (NNI). MEASUREMENTS AND MAIN RESULTS: Baseline and operative data, in-hospital outcomes, and long-term survival were compared between the NI and the NNI groups. Predictors of neurologic injury were identified. A subgroup analysis according to the type of neurologic injury was performed. Overall, NI occurred in 19% of patients in the overall series, but the proportion of patients with NI ranged from 0% to 65% among the centers. Ischemic stroke occurred in 84 patients and hemorrhagic stroke in 47 patients. Emergency procedure was the sole independent predictor of NI. In-hospital mortality was higher in the NI group than in the NNI group (79% v 61%, p < 0.001). The one-year survival was lower in the NI group (17%) compared with the NNI group (37%). Long-term survival did not differ between patients with ischemic stroke and those with hemorrhagic stroke. CONCLUSION: Neurologic injury during PC-ECMO is common and associated with a dismal prognosis. There is considerable interinstitutional variation in the proportion of neurologic injury in PC-ECMO-treated adults. Well-known risk factors for stroke are not associated with neurologic injury in this setting.
Keywords: kardiochirurgické výkony; Humans; mimotělní membránová oxygenace; Stroke; Shock, Cardiogenic; dospělí; lidé; kardiogenní šok; mortalita v nemocnicích; postcardiotomy shock; stroke; outcome; Extracorporeal Membrane Oxygenation; ischemic stroke; Cardiac Surgical Procedures; cévní mozková příhoda; Adult; extracorporeal membrane oxygenation; neurologic injury; Retrospective Studies; retrospektivní studie; intracerebral hemorrhage; Hospital Mortality